Institutionalizing Sponsored News in Legacy Media: Negotiating the Firewall and the Role of 'Roso' at Kompas Daily - Ichwan Susanto; Ignatius Haryanto; Ambang Priyonggo (ULTIMA Comm, 2025)
Digital disruption has fundamentally eroded traditional media business models, forcing legacy outlets to seek alternative revenue streams. This study analyzes the institutionalization of sponsored news, internally termed “collaborative content”, at Harian Kompas as a survival strategy. Adopting a constructivist qualitative case study approach, the research integrates semi-structured interviews with six key informants, newsroom observation, and internal document analysis to examine how the organization navigates the tension between commercial necessity and journalistic integrity.The findings reveal that Harian Kompas has formally institutionalized sponsored news by establishing a dedicated Collaborative Content Desk. This entity employs a “non-approval” mechanism to ensure editorial independence from partners, while editorial leadership utilizes “roso” (editorial intuition) as a critical ethical filter for partner and theme selection. Despite these safeguards, the study identifies persistent challenges, notably collaborators’ resistance toward transparent content labeling and the emergence of subconscious bias among field journalists. The study demonstrates that Harian Kompas, as a hybrid media organization, actively negotiates the balance between market survival and the preservation of core journalistic values in the digital era. This finding highlights how legacy institutions institutionalize sponsored content while striving to maintain editorial integrity, thereby contributing to broader discussions on the transformation of media organizations under digital disruption.